Preparation of YIG by Modified Domestic Iron Oxide - M, Mozaffari; J, Amighian (Malaysian Journal of Science, 2002)
Iron oxide by Ã¢â‚¬â€ product of a local steel Complex was modified to use for preparation of Yttrium iron garnet (YIG). The improvement was necessary to reduce impurities, especially the SiOÃ¢â€šâ€š and ClÃ¢ÂÂ» contents, which have deteriorative effects on magnetic properties and equipments used for preparation of the samples. The modified iron oxide was then mixed with Yttrium oxide of Merck Company in appropriate proportion to obtain a stoichiometric single phase YIG, using the conventional ceramic technique. XRD and SEM equipments were used to identify the resulting phases and microstructure respectively. Magnetic parameters were measured by VSM. Curie temperature of the samples was obtained by DTG (M) method. The results were compared with those obtained from samples that made by Merck iron oxide. There are small differences between the results. This was discussed according to extra pores and minute secondary phase in the samples made by domestic iron oxide.